Children then, adults now: long-term outcomes—performance at 15, 20, and 25 years of cochlear implant use - Moura, João Elói; Martins, Jorge Humberto; Alves, Marisa; Oliveira, Graça; Ramos, Daniela; Alves, Helena; Caiado, Ricardo; Teixeira, António; Silva, Luís Filipe; Migueis, Jorge (Frontiers in Rehabilitation Sciences, 2023)
Motivation: Severe to profound sensorineural hearing loss interferes with the child's development at the cognitive, linguistic, academic, and social levels. Since the beginning of the pediatric auditory rehabilitation program through cochlear implantation in the ENT Service of CHUC, its mentors defended the early diagnosis of hearing loss followed by timely intervention, and this was considered the starting point to optimize (re)habilitation through this method. After three decades, we evaluated the performance of patients implanted in the initial phase of the cochlear implantation program.The study aimed to evaluate the performance of individuals with severe to profound congenital hearing loss who underwent pediatric cochlear implantation and have used the cochlear implant for at least 25 years, to analyze the beneficial effect of early intervention in improving performance results. Methods: The study sample is composed of 31 individuals with severe to profound congenital hearing loss and no other comorbidities, divided into two groups (Group 1age at implantation under 3 years of age; Group 2 -age at implantation over 3 years). All 31 subjects were evaluated at 15, 20, and 25 years of cochlear implant (CI) use with a comprehensive set of tests. Additionally, data were collected regarding the academic level of each participant. The results of both groups were compared to find out if there is an effect of age at implantation on auditory performance, and if there is an improvement in the performance with CI over time (15, 20, and 25 years of use). Results: The results show that there is a positive effect, with statistical significance, of early implantation on auditory performance, and telephone use. In both groups, there is an increase in performance over time, but it tends to stabilize after 20 years of CI use.The results obtained in this work support the importance of early intervention in patients with severe to profound hearing loss who are cochlear implant users and show that CI is an effective and reliable method in the treatment of these patients, contributing to a better socio-educational integration of these patients, and that the benefits last over time.